Axon‐Myelin Unit Blistering as Early Event in MS Normal Appearing White Matter. Issue 4 (27th January 2021) - Luchicchi, Antonio; Hart, Bert't; Frigerio, Irene; van Dam, Anne‐Marie; Perna, Laura; Offerhaus, Herman L.; Stys, Peter K.; Schenk, Geert J.; Geurts, Jeroen J. G.
Abstract : Objective: Multiple sclerosis (MS) is a chronic neuroinflammatory and neurodegenerative disease of unknown etiology. Although the prevalent view regards a CD4 + ‐lymphocyte autoimmune reaction against myelin at the root of the disease, recent studies propose autoimmunity as a secondary reaction to idiopathic brain damage. To gain knowledge about this possibility we investigated the presence of axonal and myelinic morphological alterations, which could implicate imbalance of axon‐myelin units as primary event in MS pathogenesis. Methods: Using high resolution imaging histological brain specimens from patients with MS and non‐neurological/non‐MS controls, we explored molecular changes underpinning imbalanced interaction between axon and myelin in normal appearing white matter (NAWM), a region characterized by normal myelination and absent inflammatory activity. Results: In MS brains, we detected blister‐like swellings formed by myelin detachment from axons, which were substantially less frequently retrieved in non‐neurological/non‐MS controls. Swellings in MS NAWM presented altered glutamate receptor expression, myelin associated glycoprotein (MAG) distribution, and lipid biochemical composition of myelin sheaths. Changes in tethering protein expression, widening of nodes of Ranvier and altered distribution of sodium channels in nodal regions of otherwise normally myelinated axons were also present in MS NAWM. Finally, we demonstrate a significant increase, compared with controls, in citrullinated proteins in myelin of MS cases, pointing toward biochemical modifications that may amplify the immunogenicity of MS myelin. Interpretation: Collectively, the impaired interaction of myelin and axons potentially leads to myelin disintegration. Conceptually, the ensuing release of (post‐translationally modified) myelin antigens may elicit a subsequent immune attack in MS. ANN NEUROL 2021;89:711–725